2021
DOI: 10.3389/fmicb.2021.659736
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Insecticidal Protein (Vip): A Potential Contender From Bacillus thuringiensis for Efficient Management of Various Detrimental Agricultural Pests

Abstract: Bacillus thuringiensis (Bt) bacterium is found in various ecological habitats, and has natural entomo-pesticidal properties, due to the production of crystalline and soluble proteins during different growth phases. In addition to Cry and Cyt proteins, this bacterium also produces Vegetative insecticidal protein (Vip) during its vegetative growth phase, which is considered an excellent toxic candidate because of the difference in sequence homology and receptor sites from Cry proteins. Vip proteins are referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 210 publications
(307 reference statements)
2
42
0
Order By: Relevance
“…Analysis of SEC purified fractions revealed that the native molecular weight of Vip3Aa was 669 kDa, which may have an oligomeric structure of at least an octamer or more or an irregular highly aggregated structure ( Figure 1 A). It is known that the C-terminus of Vip3A proteins are cleaved by midgut proteases to produce a 62–66 kDa protease-resistant toxic core [ 8 , 23 ]. Recently, an approximately 340 kDa homo-tetramer structure has been identified from Vip3A digested by trypsin or insect midgut proteases [ 19 , 21 , 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of SEC purified fractions revealed that the native molecular weight of Vip3Aa was 669 kDa, which may have an oligomeric structure of at least an octamer or more or an irregular highly aggregated structure ( Figure 1 A). It is known that the C-terminus of Vip3A proteins are cleaved by midgut proteases to produce a 62–66 kDa protease-resistant toxic core [ 8 , 23 ]. Recently, an approximately 340 kDa homo-tetramer structure has been identified from Vip3A digested by trypsin or insect midgut proteases [ 19 , 21 , 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vip proteins are released during vegetative growth and have no resemblance to Cry toxins. Until recently, the Vip protein family was divided into four categories: Vip1, Vip2, Vip3, and Vip4 [ 8 ]. Vip1 and Vip2 proteins are the two parts of a binary toxin, which is toxic to coleopterans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three subfamilies of Vip proteins. Vip1 and Vip2 heterodimer toxins, effective against pests belonging to Hemiptera and Coleoptera orders, whereas Vip3, the most extensively studied family of Vip toxins have toxicity toward Lepidopterans et al Vip proteins are also known as second-generation insecticidal proteins, that can be used either alone or in combination with cry proteins to control a number of insect-pests ( Gupta et al, 2021 ). In terms of toxicity potential against susceptible insects, these Vip3 proteins are comparable to cry proteins.…”
Section: Biotechnological Approaches In Insect Pest Managementmentioning
confidence: 99%
“…Vegetative insecticidal proteins 3A (Vip3A), secreted from Bacillus thuringiensis (Bt) during their vegetative growth stage, are important insecticidal proteins that show toxicity against a wide variety of lepidopteran pests (Chakrabarty et al, 2020;Gupta et al, 2021). It was worth mentioning that Vip3A proteins displayed synergistic effect when coupling with Cry toxins for the control of agricultural pests (Wang et al, 2020;Lemes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%